Peran Edukasi dan Pemeriksaan Tekanan Darah dalam Upaya Pencegahan Hipertensi di Cengkareng - Robert Kosasih; Alexander HalimSantoso; Edwin Destra; Dianova Soeltanong (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
Hypertension is one of the leading causes of cardiovascular morbidity and mortality. Excessive sodium intake is known to contribute to increased blood pressure through certain physiopathological mechanisms. The purpose of this activity is to evaluate the distribution of blood pressure and the role of education on sodium intake restriction in community screening activities. The activity was carried out at the Cengkareng Baptist Foundation School with the Plan-Do-Check-Act (PDCA) approach. Blood pressure examinations were carried out using an automatic digital tensiometer on 57 adult participants. Data were classified according to blood pressure category, and all participants received education on sodium intake restriction. The results showed that the average systolic and diastolic pressures were 132.4 mmHg and 87.64 mmHg, respectively. Most participants were categorized as pre-hypertension and hypertension. Education on sodium intake restriction is important in hypertension prevention strategies at the community level and needs to be integrated into early detection programs.